Cyclic Performance of Precast Concrete Columns Using Steel Box Connection - Chayanon Hansapinyo (2018)
© 2017, Iran University of Science and Technology. This paper presents an evaluation on lateral cyclic behaviors of precast concrete columns using a steel box connection through experimental investigation. The test consisted of one monolithic reinforced concrete column as a reference and five precast concrete columns. All specimens had identical dimensions of 0.25 × 0.25 m 2 cross-sectional area and 1.7 m height with a longitudinal reinforcement ratio of 0.0152. Materials used for all specimens were also from the same batch. The study was aimed at understanding the design concept of the steel connecting box and detailing of column reinforcement for avoiding the brittle failure of precast concrete frame buildings. The experimental results show that without premature failure in welding or nut slipping, depending largely on the reinforcement details, the precast system with a steel box connection can be effectively used. Flexural failure mode with a ductile mechanism can be achieved to resemble the monolithic one. With a higher relative stiffness and capacities of the designed connecting box, the precast columns show a higher capacity as the failure section was shifted to an upper level. Hence, it can be said that the proper details of precast concrete columns contain acceptable seismic performances, e.g. ultimate capacity, stiffness, energy dissipation, and capacity degradation under repeated loading.